APLIKASI KLASIFIKASI INDUSTRI TAAT DAN TIDAK TAAT DI WILAYAH SEMARANG BERBASIS WEBGIS (Information Technology and Telematics, 2015)
Abstract  -  Management of environment is an obligation that  must  be  done  and  also  a  responsibility  for  those initiators  of  any  activities  and  also  the  society.  It  is because within the process of industrialization, it will not cause  or  trigger  an  environmental  pollution,  which  in this  case  is  disposal  of  wastes  that  do  not  meet  quality standards. To solve  that problem there will be  needed  formanaging the  provisions of  the legislation  and  licensingrequirements  associated  with  pollution.  Basically, managing the  provisions of  the legislation  and  licensingrequirements  are  done  ever  since  the  industries  are opened.  however,  in  fact,  many  of  industries  are  still disobedient. This  classification  of  obedience  and disobedience  industries  application  aims  to  help environment agency to clssified obedient industries and those  which  are  not,  in  Semarang  regency,  this application  is  built  to  show  industrial  classification  of obedient  industries,  disobedient  industries,  location detection  to  detects  the  objet  by  using  Google  services, and direction to guide the user from his/her place to the location  of  industry.  This  application  is  shown  in  the form  of  WebGis  based  thematic  map  by  using  Google Map Api. Keywords : Classification, Obedience, Disobedience,